Adsorption of arsenic using low cost adsorbents: Guava leaf biomass, mango bark and bagasse - Mohan D.; Markandeya; Dey S.; Dwivedi S.B.; Shukla S.P. (My University, 2025)
Adsorbents prepared from inexpensive materials of guava leaf biomass, mango bark and bagasse were studied for As(III) removal from the aqueous solution. The effects of pH, contact time, initial As(III) concentration and adsorbent dosage on the adsorption of As(III) were studied using batch experiments. Adsorption process was also verified with Langmuir, Freundlich, Temkin and Redlich-Peterson models. Langmuir isotherm fitted best in the experimental data. Application of Langmuir isotherm to the system yielded the maximum capacities of 1.35 mg g-1, 1.25 mg g-1 and 1.05 mg g-1 for bagasse, mango bark and guava leaf biomass respectively, in the range of As(III) concentration as 10-140 mg l-1. The dimensionless equilibrium parameter, RL, signifies favourable adsorption of As(III) on all adsorbents and was observed to be in the range of 0.029-0.294, 0.021- 0.235 and 0.021-0.234, for bagasse, mango bark and guava leaf biomass respectively (0 < RL < 1). The adsorption process was observed to follow pseudosecond- order kinetic model. © 2019 Current Science Association, Bengaluru.